2016
DOI: 10.5857/rcp.2016.5.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Photoacid Catalyzed Reaction of Phenol with Styrene

Abstract: ABSTRACT:The reaction of styrene with phenol using photoacid catalyst has been investigated. Upon irradiation with 450 nm light, protonated merocyanine photoacid converts into spiropyran form with releasing proton. The reaction of styrene with phenol has been conducted under irradiation with 450 nm light using merocyanine photoacid catalyst at room temperature in comparison with the results using some selected catalysts including H 2 SO 4 or FeCl 3 at the reaction temperature of 120 o C.Sterically hindered phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Lei’s and Kokotos’s group reported that 2 or eosin Y 3 could catalyze the acetalization reaction (Scheme c). , Wang’s group discovered a stereoselective synthesis of 2-deoxyglycosides from glycals using 3 and diphenyl disulfide as the catalyst (Scheme d) . Regardless of these impressive achievements, the excited-state proton transfer (ESPT) photoacid catalysts are still challenging to provoke many acid-catalyzed reactions because the free protons of the ESPTs could recombine very fast with the corresponding conjugated bases in the ground state (Scheme e) . To achieve a significant increase in the proton concentration under visible light irradiation, metastable-state photoacids such as MEH were discovered and thrived (Scheme f) .…”
mentioning
confidence: 99%
“…Lei’s and Kokotos’s group reported that 2 or eosin Y 3 could catalyze the acetalization reaction (Scheme c). , Wang’s group discovered a stereoselective synthesis of 2-deoxyglycosides from glycals using 3 and diphenyl disulfide as the catalyst (Scheme d) . Regardless of these impressive achievements, the excited-state proton transfer (ESPT) photoacid catalysts are still challenging to provoke many acid-catalyzed reactions because the free protons of the ESPTs could recombine very fast with the corresponding conjugated bases in the ground state (Scheme e) . To achieve a significant increase in the proton concentration under visible light irradiation, metastable-state photoacids such as MEH were discovered and thrived (Scheme f) .…”
mentioning
confidence: 99%